The Effect of Smartphone Usage Intensity on Students’ Learning Discipline at MTs Miftahul Ulum, East Lampung - Bahrudin; Sugiarto; Roudhotul Jannah, Siti (Journal of Research in Islamic Education, 2026)
This study aims to analyze the effect of smartphone usage intensity on students’ learning discipline at MTs Miftahul Ulum, East Lampung. The research employed a quantitative approach with a cross-sectional survey design. The population consisted of 164 students, with a sample of 122 respondents selected using a simple random sampling technique. Data were collected through a Likert-scale questionnaire measuring smartphone usage intensity and learning discipline. Data analysis was conducted using normality tests, linearity tests, simple linear regression, hypothesis testing (t-test), and the coefficient of determination with the assistance of SPSS.The results indicate that smartphone usage intensity does not have a significant effect on students’ learning discipline, as shown by a significance value of 0.236 (> 0.05) and a coefficient of determination of 1.2%. These findings suggest that learning discipline is not directly influenced by smartphone usage intensity, but rather by other factors such as self-control, learning motivation, and the educational environment. This study contributes novel insights by examining this relationship within the context of a madrasah, which has distinct religious characteristics. The implication of this study highlights the importance of managing smartphone use in a wise and educational manner to support the learning process.